Hubungan Pengetahuan Gizi dengan Indeks Massa Tubuh Pada Mahasiswa MSIB SEAMEO RECFON - Romadhona, Evin Shafira; Elvandari, Millyantri (Innovative: Journal Of Social Science Research, 2024)
The role of students in dedicating themselves to becoming students is very important. The Certified Internship & Independent Study Program (MSIB) has more benefits compared to other Merdeka Campus programs, namely sustainable career prospects that give students the opportunity to be accepted as intern employees. Body Mass Index (BMI) is a simple method to monitor the nutritional status of adults, especially in the context of underweight or overweight conditions. This study design is cross-sectional, which is a research method that takes samples from a certain population through observation at a certain time and is descriptive in nature. This study was conducted on Friday, April 19, 2024, at Universitas Indonesia Salemba. The variables studied in this research are nutritional status and knowledge about nutrition. Data collection was carried out through direct measurement. After the intervention, nutritional knowledge increased significantly with 37 subjects (71.1%) falling into the good category for nutritional knowledge level.